PERANAN RESEARCHAND DEVELOPMENT (R&D) DAN STRUCTURAL EQUATIONMODEL (SEM) DALAM PENELITIAN PENGEMBANGAN KURIKULUM TINGKAT SATUAN PENDIDIKAN - Rosana, Dadan (LPMPP Universitas Negeri Yogyakarta, 2008)
A curriculum consistsof a number of interrelated complex components. Theschool-based curriculum has several components: curriculumand learningoutcomes, class-based evaluation, teaching-learning activities,and school-basedcurriculum organization. These are completedwith the establishment ofcurriculum networking, the development of curriculum supplements (e.g.syllabuses), professional trainings for educational practitioners,and thedevelopmentof curriculum information system. The school-based curriculumimplementationand development strategies should include all of them. Therefore,it is necessary to continuously conduct researchon the school-based curriculum,especiallywhen the curriculum starts to be implemented. There are two importantpoints in the school-based curriculum development research. The first includesdevelopingand validating all the instructional kits used in the school to ensure that- the kits are ready to use and effective, and the second involves the comprehensiveanalysisof all the variables influencing the success of education. For the first point,the.researchand development (R&D) approach is appropriate in the developmentand validation of curriculum supplements. For the second point, regarding causalcorrelations among variables in education, the structural equation modeling isappropriate. There are anumber of educational variables that cannot be directlymeasured; latent variablesmust be formulated through other measurable variables.If the variables cannot be directly measured,we have to form the variables bymeans of variable indicators that can be directly measured by using measurementmodeling. Analyzing causal correlations among latent variables,we can use thestructural equation modeling involvingpath analysis and measurement modeling